Engineering the primary and second coordination sphere of metal-organic framework boosts the peroxidase-like activity - Xin Yuan; Xinghua Chen; Jun Xiong; Yifang Cao; Niya Ta; Ruichen Gao; Shuli Liu; Min-Hua Zong; Xiaoling Wu; Wen-Yong Lou (Chemical Engineering Journal, 2025)

Decoupling physicochemical-biological dynamics in marine oil spills: early adaptive microbial response to hydrodynamic forcing unveils zonal impact gradients - Ranran Dong; Xinping Wang; Ruichen Cao; Chunhui Wang; Fengshu Li; Zhifeng Wan; Peiyan Sun; Mutai Bao; Haoshuai Li (Journal of Hazardous Materials, 2025)

Three-dimensional simulation of wave-induced seabed liquefaction in the Chengdao area - Youqi Wang; Shengyi Jiao; Haibo Chen; Ruichen Cao; Xianqing Lv (Ocean Engineering, 2025)

Serum polychlorinated biphenyls as a risk factor for MASLD: Exploring the association and underlying mechanisms - Ruichen Yang; Qingqing Jiang; Wentao Liu; Furong Wang; Shiyi Cao (Science of The Total Environment, 2025)

Oil pollution risks on coastlines in the Eastern China Seas - Ruichen Cao; Junting Guo; Zengrui Rong; Haibo Chen; Xianqing Lv (Environmental Pollution, 2025)

Oil Spill Occurrence and Pollution Risk Assessment Based on Sea State, Oil Platform Location, and Shipping Route Density in the Bohai Sea - Tao Liu; Ruichen Cao; Minxia Zhang; Xing Chen; Fan Bi; Jiangling Xu (Journal of Marine Science and Engineering, 2025)
The Bohai Sea is the only semi-enclosed inland sea in China. With active marine economic activities, it faces a persistently high risk of oil spill accidents. This study assesses the occurrence risk and pollution risk of oil spills by considering factors such as sea state, the location of oil platform, and shipping route density in the Bohai Sea. The results show that the central part of the Bohai Sea, the southern Liaodong Peninsula, and the Bohai Strait area have a relatively high occurrence risk of oil spills due to busy maritime traffic and harsh sea conditions. In contrast, some areas in the northern, western, and southern parts of the Bohai Sea have a relatively low occurrence risk of oil spills because of weak maritime activity intensity and relatively calm sea state. In terms of the oil pollution risk, its distribution in the Bohai Sea shows significant seasonal characteristics, which are mainly comprehensively affected by multiple dynamic factors such as circulation, monsoon, and seawater exchange. Based on the oil pollution risk distribution, seasonally targeted strategies are proposed, which can provide a scientific basis for oil spill prevention and emergency management in the Bohai Sea, and help relevant departments formulate targeted prevention and control strategies.

Multi-temporal landslide inventory mapping after wildfire and implications for post-fire debris flow activity - Ruichen Zhou; Kun He; Xiewen Hu; Xichao Cao; Chuanjie Xi; Yonghao Zhou; Xueqiang Gong; Lin Deng (Engineering Geology, 2025)

The Effect of Model Input Uncertainty on the Simulation of Typical Pollutant Transport in the Coastal Waters of China - Nan Wang; Zihan Zhao; Ruichen Cao; Xianqing Lv; Honghua Shi (Journal of Marine Science and Engineering, 2024)
Route planning to evade potential pollution holds critical importance for aquaculture vessels. This study establishes a fish-feed pollutant drift model based on the Lagrangian particle tracking algorithm and designs four sets of sensitivity experiments in the East China Sea. The research investigates the impact of model input uncertainties on the drift trajectory, centroid position, and sweeping area of the fish-feed pollutants. Numerical results indicate that the uncertainty in the background flow field significantly affects the uncertainty in the centroid position and sweeping area in the numerical simulations. Specifically, when a 35% random error is added to the background flow field, the centroid shift distance reaches its maximum, and the sweeping area also attains its largest value. The uncertainty in the background wind field affects the centroid position of particles but to a much lesser extent compared to the background flow field. When considering only the uncertainty of the background wind field, the sweeping area does not significantly differ from the control experiment as the uncertainty of the background wind field increases. The initial release position has little effect on the drift direction of the fish-feed pollutants but does affect the drift distance; it has minimal impact on the trajectory but significantly affects the final position of the pollutant centroid. By analyzing the model uncertainties, this study reveals the key factors influencing the drift of fish-feed pollutants. This information is crucial for aquaculture vessels in planning routes, considering environmental factors, and reducing potential pollution risks.

Research on scallop shells transport of the Yantai coastal region in the Bohai Sea - Le Chen; Yibo Zhang; Yongzhi Liu; Ruichen Cao; Xianqing Lv (Frontiers in Marine Science, 2024)
Introduction Bivalve aquaculture is an important pillar of China's fisheries, with over 1 million tonnes of scallop shells produced annually. However, most of these shells are directly discarded into the sea, leading to continuous pollution of the marine and coastal environments, especially the coast of Yantai in the Bohai Sea where a large number of discarded scallop shell have accumulated. Methods To trace the fate of scallop shells in the ocean, this study established a model for the transport of scallop shells, coupling a two-dimensional tidal current model using the adjoint method with a Lagrangian particle model. By simulating nested tidal models, the distribution of tidal residual current in the Yantai coastal region was obtained. Then, a Lagrangian particle model was used to track the transport pathways of pollutants in the sea. Results Driven by the residual current calculated from the tidal model with the actual situation, possible pollutant release areas were inferred. The results of Lagrangian particle tracking experiments indicate that pollutants were released from the upstream accumulation area, specifically the area near Penglai Hulushan, confirming previous speculation. Discussion The scallop shells transport model can accurately simulate the spatiotemporal profile of scallop shells, which is helpful for managing scallop shell resources and improving the level of shell reuse.

Combined InSAR and optical dataset unravelling the characteristics of hillslope erosion in burned areas in Xichang, China - Xichao Cao; Kun He; Xiewen Hu; Gang Luo; Yonghao Zhou; Ruichen Zhou; Ying Yang; Tao Jin (CATENA, 2024)

Glacial debris flow susceptibility mapping based on combined models in the Parlung Tsangpo Basin, China - Yonghao Zhou; Xiewen Hu; Chuanjie Xi; Hong Wen; Xichao Cao; Tao Jin; Ruichen Zhou; Yu Zhang; Xueqiang Gong (Journal of Mountain Science, 2024)

Regional to global assessments of ocean transparency dynamics from 1997 to 2019 - Junting Guo; Zihan Zhao; Ruichen Cao; Xianqing Lv (Progress in Oceanography, 2023)

Modeling the long-term transport and fate of oil spilled from the 2021 A Symphony tanker collision in the Yellow Sea, China: Reliability of the stochastic simulation - Ruichen Cao; Zengrui Rong; Haibo Chen; Yi Liu; Lin Mu; Xianqing Lv (Ocean Modelling, 2023)

Research on the Transport of Typical Pollutants in the Yellow Sea with Flow and Wind Fields - Nan Wang; Ruichen Cao; Xianqing Lv; Honghua Shi (Journal of Marine Science and Engineering, 2023)
In this study, we developed a transport model for typical pollutants in the Yellow Sea using the Lagrangian particle tracking method to analyze the trajectories of fish feed, a common pollutant in the Yellow Sea. The model incorporates the influence of ocean currents and surface winds on pollutant transport and utilizes a series of numerical experiments to simulate pollutant transport. Through statistical analysis of the numerical experiment results, we identified characteristic circles that represent the pollutant distribution patterns. Furthermore, based on the current and wind information within these characteristic circles, we derived an empirical formula to describe pollutant distribution. This formula enables us to predict the spatial distribution of pollutants using available current and wind data. Using this empirical formula, we designed an effective path to avoid pollutant contamination. This approach not only optimizes the utilization of computational resources within the study area but also contributes to the rational planning of navigation routes for aquaculture vessels. Overall, our study provides valuable insights into the transport behavior of fish feed pollutants in the Yellow Sea. The establishment of the empirical formula and the design of effective routes to avoid pollution contribute to the efficient management of pollution and facilitate the planning of marine activities in the region.

The liquefaction pressure characteristics of silty soil in the Chengdao area: Numerical simulations - Qixiang Wang; Yupeng Ren; Ruichen Cao; Guohui Xu; Xianqing Lv (Ocean Engineering, 2023)

Triclocarban exposure aggravates dextran sulfate sodium-induced colitis by deteriorating the gut barrier function and microbial community in mice - Mengyu Qin; Hehua Lei; Yuchen Song; Mengjing Wu; Chuan Chen; Zheng Cao; Cui Zhang; Ruichen Du; Ce Zhang; Xian Wang; Limin Zhang (Food and Chemical Toxicology, 2023)